The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/modpathol.3800168
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between karyotype and quantitative immunophenotype in acute myelogenous leukemia with t(8;21)

Abstract: Acute myelogenous leukemia with t(8;21) is a distinct clinicopathologic entity in which the malignant myeloblasts display a characteristic pattern of surface antigen expression. Quantitative analysis of surface marker expression in patients with this chromosomal abnormality compared to acute myelogenous leukemia patients with a different karyotype has not been reported. From 305 consecutive newly diagnosed acute myelogenous leukemia patients underwent immunophenotyping and cytogenetic analysis at our center; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…In accordance with a previous report, 55 we observed low CD33 expression levels in blasts of patients with t(8;21). Another recent study reported higher CD33 expression in AMLs with NPM1 mutation, 56 which is confirmed by our findings.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with a previous report, 55 we observed low CD33 expression levels in blasts of patients with t(8;21). Another recent study reported higher CD33 expression in AMLs with NPM1 mutation, 56 which is confirmed by our findings.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study reported that CD34 was expressed in 62% of non-APL and 17% of APL (all microgranular variants) cases [17]. In the present study, CD34 expression was significantly less frequent in APL cases than in non-APL.…”
Section: Disussionmentioning
confidence: 32%
“…Furthermore, HLA-DR negative non-APL showed a lower incidence of CD34 expression than did Another study also demonstrated that the incidence of CD34 expression was higher in HLA-DR positive non-APL (79%) than in HLA-DR negative non-APL patients (17%) [18]. Especially, 10% of non-APL patients were negative for both CD34 and HLA-DR [17]. One author reported that invaginated nuclear morphology was associated with loss of HLA-DR and CD34 expressions in non-APL [19].…”
Section: Disussionmentioning
confidence: 83%
“…This protein, AML1-ETO, act as a negative dominant inhibitor of wild-type AML1 [27], which theoretically could lead to down-regulation of AML1 target genes, such as MPO gene. However, blasts with t(8;21) have been shown to display higher levels of MPO expression both in clinical samples and in vitro experiments [28,29], CEBPA mutations are associated with a relatively favorable outcome, and it was recently shown in a multivariable analysis including cytogenetic risk and the FLT3-ITD and NPM1 mutations that the CEBPA double-mut genotype is associated with favorable overall and event-free survival [15][16]. In a cohort of 60 cases of adult de novo AML, we identified 1 CEBPA single-mut case and 10 CEBPA double-mut cases, and in line with previous reports, our study tended to show better overall survival in CEBPA double-mut cases compared to cases with wild-type CEBPA in patients treated with intensive chemotherapy.…”
Section: Discussionmentioning
confidence: 99%